An Observational Study of Inhaled‐Treprostinil Respiratory‐Related Safety in Patients with Pulmonary Arterial Hypertension. (1st September 2016) - Zamanian, R. T.; Levine, D. J.; Bourge, R. C.; De Souza, S. A.; Rosenzweig, E. B.; Alnuaimat, H.; Burger, C.; Mathai, S. C.; Leedom, N.; DeAngelis, K.; Lim, A.; De Marco, T.
Abstract : Inhaled treprostinil (Tyvaso) has been shown to be a safe and effective addition to pulmonary arterial hypertension (PAH) oral therapies; however, the respiratory‐related safety profile of inhaled treprostinil required further elucidation in the setting of routine clinical care. The objectives of this study were to characterize respiratory‐related adverse events (AEs) associated with current or recent treatment with inhaled treprostinil and to compare the incidence of respiratory‐related AEs in PAH patients treated with inhaled treprostinil with that in patients treated with other Food and Drug Administration (FDA)–approved PAH therapies. This was a long‐term, prospective, observational study. All respiratory‐related AEs were recorded during the study. The number of PAH patients enrolled was 1, 333, 666 treated with inhaled treprostinil and 667 controls (treated with an FDA‐approved PAH therapy other than inhaled treprostinil), for a total of 958 and 1, 094 patient‐years of exposure, respectively. In the inhaled‐treprostinil group, 1, 281 respiratory‐related AEs were reported in 403 patients (61%), and in the control group, 1, 295 respiratory‐related AEs were reported in 388 patients (58%). Cough, throat irritation, nasal discomfort, and hemoptysis were the most common respiratory‐related AEs (occurring in ≥2% of patients in either treatment group) that demonstrated a higher number of events per patient‐year of exposure in the inhaled‐treprostinil group than in the control group (risk ratio [95% confidence interval]: 1.487 [1.172–1.887], 3.777 [2.050–6.956], 2.039 [1.072–3.879], and 1.957 [1.024–3.741], respectively). Overall, inhaled treprostinil was well tolerated by PAH patients in routine clinical care, with respiratory‐related AEs consistent with the known safety profile (trial registration: clinicaltrials.gov identifier: NCT01266265).